Becoming a Church That Is Heard: A Mission Paradigm for Generation Z Hungry for Meaning - Revalyna Natasya Sara Aomo; Cindy Niatang; Natasya Talete; Mario Kahimpong (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2025)
This article explores the paradigm of church missions in reaching Generation Z, known as the digital generation hungry for meaning. The main challenge faced is the irrelevance of traditional, institutional, and dogmatic missionary approaches, which fail to address the emotional and spiritual needs of Generation Z. The aim of this research is to identify and propose more participatory and dialogical missionary methods, as well as leverage digital technology to build authentic communities. The method used is qualitative research with a descriptive-analytical approach, involving literature review and narrative analysis. The main findings indicate that the church needs to transform from merely delivering messages to listening and guiding, and creating interactive spaces that allow Generation Z to actively engage. Thus, the church can become a community that is inhabited, not just a place that is visited, where each individual feels accepted and has space to grow in faith. In conclusion, to remain relevant in the digital age, the church must adopt a new mission paradigm that focuses on consistent and meaningful presence in the lives of Generation Z, so that it can become a voice that is heard and provides hope and meaning in their lives.